Waiting to be heard : a memoir - Knox, Amanda, frey50
This is the author's account of her hard-fought battle to overcome injustice and win the freedom she deserved after spending four years in prison for the murder of Meredith Kercher in Perugia, Italy. She spent four years in a foreign prison for a crime she did not commit. Separated from her family, she was demonized by the international press and treated harshly by the Italian justice system, including disdainful police. She endured humiliation, injustice, and loneliness thousands of miles from her home. Now the young American exchange student tells the full story of her harrowing ordeal in Italy.
Prologue : December 4, 2009, Perugia, Italy -- pt. 1. Perugia -- pt. 2. Capanne I -- pt. 3. Capanne II -- Epilogue : October 3-4, 2011.
Keywords: Knox, Amanda -- Trials, litigation, etc; Sollecito, Raffaele -- Trials, litigation, etc; Kercher, Meredith -- Death and burial; Trials (Murder) -- Italy; Murder -- Investigation -- Italy -- Perugia; Murder -- Italy -- Perugia; Homicide investigation -- Italy